Recursos didácticos en la Enseñanza de Probabilidades en Educación Básica Media en la Escuela “Miguel Riofrío”, periodo 2023-2024 - Eras Guamán, Daniela Estefanía (2024)
The present research entitled: Didactic Resources in the Teaching of Probabilities in Basic Secondary Education at the "Miguel Riofrío" School, period 2023-2024, had the general objective of determining the influence of didactic resources on the teaching of probabilities in the Basic Secondary Education level at the "Miguel Riofrío" Basic Education School. The study has a Quantitative Descriptive approach with a Non-Experimental, Cross-sectional design. Various methods were employed in the research process, including the hermeneutic, inductive, deductive, analytical, synthetic, and statistical methods. For data collection, interviews were conducted with teachers and authorities, a survey was administered to teachers. An observation sheet, and a validation rubric were used, all these instruments were used to ensure that the obtained data were solid and validated the conducted research. The investigated population comprised all the teachers of the Basic Secondary level, totaling 4 people. The study aims to understand the problems teachers face when teaching Probability content and how didactic resources or tools can enhance their pedagogical work, thus empowering them in their teaching role. After applying the instruments and obtaining results from the identified problem, the teachers validated the proposed guide for the possible solution to strengthen the teaching of Probability. The results were significantly positive, with teachers indicating that didactic resources are valuable elements for their work, as they provide practical learning opportunities characterized by their dynamism and effectiveness.